Carbon fiber reinforced liquid metal matrix composite, method of making and use thereof
Patent Information
- Application Number
- CN202611292976.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-25
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]参见公开号为CN113402288A的专利公开了一种碳纤维增强的高强度、高导热复合膜制备方法,其通过将碳纤维与导热填料复合,制备了兼具高强度和高导热性能的复合膜材料;该专利虽实现了碳纤维增强的导热复合材料,但其基体为固态树脂或碳基材料,未利用液态金属作为连续基体,因此在界面贴合性和柔性变形能力方面存在不足,也未涉及电磁屏蔽功能的集成设计
本发明宏观与微观的双尺度液态金属锁固体系,实现了对液态金属从宏观到微观的全尺度约束。
Smart Images

Figure CN122979779A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of composite material technology, specifically relating to a carbon fiber reinforced liquid metal matrix composite material, its preparation method, and its application. Background Technology
[0002] With the rapid development of 5G / 6G communication, artificial intelligence, high-performance computing, and aerospace electronics, the integration and power density of electronic devices have increased dramatically, and heat flux density has exceeded 1000 W / cm². 2 Traditional silicon-based thermal greases and metal foil thermal interface materials are no longer sufficient to meet extreme heat dissipation requirements. Meanwhile, electromagnetic interference (EMI) problems generated by high-frequency electronic devices are becoming increasingly serious, creating an urgent need for novel thermal management materials that combine high thermal conductivity and high electromagnetic shielding effectiveness. Liquid metals, as a class of low-melting-point alloys, are liquid near room temperature and possess intrinsic thermal conductivity far exceeding that of traditional thermal interface materials, as well as excellent electrical conductivity, making them a research hotspot in the field of thermal management in recent years.
[0003] See patent CN108457079A, which discloses a liquid metal / carbon fiber composite material, its preparation method, and its application. This material prepares a composite material with uniform physical properties, flexibility, and good electromagnetic shielding performance by spraying a liquid metal layer onto the surface of a carbon fiber matrix. The electromagnetic wave shielding performance in the 30MHz-1.5GHz frequency band reaches more than 66.2dB. However, this patent uses a simple surface spraying process, where the liquid metal is only coated on the surface of the carbon fiber without forming a three-dimensional continuous matrix or involving interface gradient structure design. This results in deficiencies in thermal cycling stability and interfacial bonding strength.
[0004] See patent CN116554842A, which discloses a liquid metal thermal interface material and its preparation method. It slows down the alloying speed between liquid metal and metal particles by forming a metal-polyphenol nano-coating on the surface of metal particle filler as a diffusion barrier, thereby enhancing the stability of the composite material. Although this patent improves the thermal conductivity and stability of liquid metal composite materials, its technical solution mainly focuses on the chemical modification of the interface coating. It does not involve the three-dimensional braided skeleton structure of carbon fiber reinforcement, nor does it utilize gradient metal coating to achieve in-situ interface reaction. It has limitations in terms of mechanical support and liquid metal locking.
[0005] See the patent with publication number CN113402288A, which discloses a method for preparing a high-strength, high-thermal-conductivity composite film reinforced with carbon fiber. It prepares a composite film material with both high strength and high thermal conductivity by combining carbon fiber with thermally conductive filler. Although this patent realizes a thermally conductive composite material reinforced with carbon fiber, its matrix is a solid resin or carbon-based material, and it does not use liquid metal as a continuous matrix. Therefore, it has shortcomings in terms of interface adhesion and flexible deformation capability, and it does not involve the integrated design of electromagnetic shielding function. Summary of the Invention
[0006] One objective of this invention is to provide a carbon fiber reinforced liquid metal matrix composite material, which constructs a gradient transition layer in situ through the differentiated reactive activity of Cu-Ni gradient coating, and combines a dual-scale liquid metal locking system of macroscopic woven skeleton and microscopic CNT aerogel network to achieve a high degree of integration and synergistic optimization of thermal conductivity, electromagnetic shielding and mechanical properties.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A carbon fiber reinforced liquid metal matrix composite material, comprising: Liquid metal matrix: Contains 50-68 wt% GaInSn eutectic alloy; Carbon fiber reinforcement: containing 30-45 wt% carbon fiber, wherein the surface of the carbon fiber has a Cu-Ni coating, the Cu-Ni coating comprising a Cu layer and a Ni layer, wherein the Cu layer is formed on the surface of the carbon fiber, the Ni layer is formed on the surface of the Cu layer, and the thickness of the Cu layer is less than the thickness of the Ni layer; Carbon nanotube aerogel: comprising 0.5-3 wt% carbon nanotube aerogel, wherein the carbon nanotube aerogel is used to distribute in the gaps of the carbon fiber reinforcement; Magnetic responsive particles: comprising 0.1-1 wt% Ni particles, wherein the Ni particles are dispersed in the liquid metal matrix.
[0008] Preferably, the GaInSn eutectic alloy comprises Ga: 60-70%, In: 20-25%, and Sn: 10-15%. Ga, as a base component, provides low melting point and high thermal conductivity; In, as a melting point regulating element, ensures eutectic formation and improved wettability; and Sn, as a eutectic stabilizer, provides thermal stability and anti-leakage properties. These three components work synergistically to form a matrix alloy system that combines low melting point, high thermal conductivity, and good chemical stability.
[0009] Preferably, the liquid metal matrix further comprises at least one of Zn: 0.5-2wt% and Ag: 0.1-0.5wt%, wherein Zn is used to adjust the melting point and Ag is used to improve thermal conductivity.
[0010] Preferably, in the above technical solution, the carbon fiber reinforcement has a single carbon fiber filament diameter of 6-8 μm and a density of 1.6-1.80 g / cm³. 3 .
[0011] Preferably, in the above technical solution, the Cu layer has a thickness of 0.2-0.5 μm, and the Ni layer has a thickness of 0.5-2.0 μm.
[0012] Preferably, in the above technical solution, the surface roughness Ra of the Ni layer is 0.5-2.0 μm. The surface of the Ni layer is roughened, and the roughness range realizes a dual bonding mechanism of "chemical bonding + mechanical interlocking": chemical bonding comes from the formation of NiGa3 intermetallic compounds, and mechanical interlocking comes from the physical anchoring of the liquid metal by the surface uneven structure.
[0013] Preferably, in the above technical solution, the carbon nanotube aerogel comprises multi-walled carbon nanotubes (MWCNTs), wherein the MWCNTs have an outer diameter of 10-20 nm, a length of 5-20 μm, and a specific surface area of 200-400 m². 2 / g, the outer diameter, length, and specific surface area of the multi-walled carbon nanotubes (CNTs) together determine the microscopic locking ability of the aerogel network. An outer diameter of 10-20 nm ensures sufficient mechanical strength of the tube walls to withstand impregnation shear forces; a length of 5-20 µm ensures the entanglement and connectivity between CNTs in the network, forming a continuous capillary porous system; and a specific surface area of 200-400 m² / g. 2 / g provides ample physical adsorption sites, and the three work together to enable the aerogel network to effectively perform the triple functions of capillary locking, physical adsorption, and thermal conduction supplementation.
[0014] Preferably, the average particle size of the Ni particles is 1-10 μm, and more preferably, the average particle size of the Ni particles is 3-7 μm. Ni particles in the above particle size range have sufficient magnetic moment to generate effective rotational motion in a 0.1-0.5T magnetic field, while having a moderate sedimentation rate in liquid metal (not sedimenting too quickly) and good dispersion stability (not easily agglomerating).
[0015] Another objective of this invention is to provide a method for preparing carbon fiber reinforced liquid metal matrix composites, thereby preparing carbon fiber reinforced liquid metal matrix composites with a reaction gradient interface structure of "carbon fiber → CuGa2 → NiGa3 → liquid metal".
[0016] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for preparing a carbon fiber reinforced liquid metal matrix composite material, comprising: Carbon fiber reinforcements are woven into a three-dimensional braid, and carbon nanotube aerogels are embedded in the gaps between the three-dimensional braids. After shaping and drying, a preform is obtained. Under the action of an alternating magnetic field, liquid metal containing Ni particles is vacuum pressure impregnated into a preform. The Cu-Ni coating on the carbon fiber surface reacts in situ with the liquid metal matrix at the interface to form a metallurgical bonding interface. The metallurgical bonding interface consists of CuGa2 layer and NiGa3 layer from the carbon fiber surface outward. Under the synergistic effect of magnetic field and pressure, the mixture is cooled and solidified to obtain a carbon fiber reinforced liquid metal matrix composite material.
[0017] Preferably, the preparation method further includes sequentially performing degumming, roughening, and sensitization activation treatments on the carbon fiber, preparing a Cu layer by chemical plating, and preparing a Ni layer by electroplating to obtain carbon fiber with a Cu-Ni coating on the surface.
[0018] The Cu layer is prepared by chemical plating or electroplating. Chemical plating utilizes a self-catalytic reduction reaction, which does not require an external current and is suitable for metallizing the initially non-conductive surface of carbon fibers. It is simple to operate and provides uniform coverage. Electroplating, on the other hand, requires the carbon fiber surface to be conductive before electroplating (which makes it conductive after chemical plating of Cu). It has a fast deposition rate and a dense coating.
[0019] The Ni layer is prepared by electroplating. After Cu electroless plating, the carbon fiber surface is conductive and ready for electroplating. Electroplated Ni has a deposition rate 3-5 times faster than electroless Ni plating, making it more suitable for the efficient preparation of thicker coatings (0.5-2.0µm). Electroplated Ni layers are denser and have lower porosity, providing better protection as the first barrier in contact with liquid metal.
[0020] Preferably, the preparation method further includes dispersing multi-walled carbon nanotubes in deionized water, performing hydrothermal self-assembly reaction after ultrasonic dispersion, and then freeze-drying to obtain carbon nanotube aerogel.
[0021] Preferably, in the above technical solution, the frequency of the alternating magnetic field is 10-100Hz, the magnetic field strength is 0.1-0.5T, and the alternating magnetic field is applied in the following three stages: (a) Impregnation stage: frequency 50-100Hz, intensity 0.2-0.5T, promotes the rotational movement of Ni microparticles in liquid metal, and drives the carbon fiber to oriented alignment; (b) Reaction stage: frequency 10-50Hz, intensity 0.1-0.3T, while maintaining directional alignment, accelerate interfacial diffusion reaction; (c) Curing stage: frequency 10-30Hz, intensity 0.1-0.2T, to ensure the stable formation of the gradient interface structure.
[0022] Preferably, the specific parameters of the vacuum pressure impregnation described above are as follows: the preheating temperature of the preform is 100-150℃; the melting point range of the liquid metal is 5-20℃, and its preheating temperature is 50-80℃ higher than the melting point; the vacuum degree is <10Pa, and the vacuum holding time is 10-15min; the impregnation pressure is 1-5MPa, the pressure holding time is 10-30min, and the cooling rate is 5-10℃ / min.
[0023] Preferably, the preparation method further includes a step of surface treatment of the carbon fiber reinforced liquid metal matrix composite material.
[0024] Another objective of this invention is to provide an application of carbon fiber reinforced liquid metal matrix composite material, which can be used in thermal interface materials, such as thermal management of CPUs, GPUs, power semiconductor devices, 5G base station chips or aerospace electronic equipment; it can also be used in electromagnetic shielding materials, such as electromagnetic interference protection of 5G / 6G communication equipment, military electronic equipment, medical equipment or aerospace vehicles.
[0025] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art: This invention provides a dual-scale liquid metal locking system that achieves full-scale constraint of liquid metal from macroscopic to microscopic levels.
[0026] On a macroscopic scale, the woven carbon fiber skeleton forms a rigid spatial network structure through the interweaving and mechanical interlocking of fibers. When stretched, it adapts to deformation through the reorientation and slippage of fibers. At the same time, the change in the pore morphology of the woven structure (from approximately circular to elliptical) still maintains the overall constraint on the liquid metal.
[0027] At the microscale, carbon nanotube aerogel networks play multiple locking functions: first, the large specific surface area provides strong physical adsorption force, firmly adsorbing liquid metal molecules onto the CNT surface; second, the abundant nanoscale pores generate strong capillary force; third, the CNT network constructs a microscopic "liquid reservoir" system for liquid metal, so that even if the macroscopic pores expand during deformation, the liquid metal in the microscopic reservoir can still be firmly bound by capillary force.
[0028] This invention achieves synergy and mutual promotion through material structure design: the construction of heat conduction paths simultaneously enhances electromagnetic shielding effectiveness (high thermal conductivity paths are equivalent to high electrical conductivity paths, which are beneficial for electromagnetic shielding); the integrity of the electromagnetic shielding network helps to distribute heat evenly (reducing local hot spots); the existence of the mechanical skeleton ensures the morphological stability of the heat conduction and shielding networks (preventing network breakage caused by deformation). Attached Figure Description
[0029] Appendix Figure 1This is a schematic diagram of the carbon fiber reinforced liquid metal matrix composite material in this embodiment; Appendix Figure 2 This is a schematic diagram of the magnetic field orientation of Ni particles in this embodiment.
[0030] In the attached diagrams above: Detailed Implementation
[0031] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0032] like Figure 1 , 2 The image shows a carbon fiber reinforced liquid metal matrix composite material, comprising a liquid metal matrix, a carbon fiber reinforcement, carbon nanotube aerogel, and magnetically responsive particles. By total mass of the composite material: the liquid metal matrix contains 50-68 wt% GaInSn eutectic alloy, the carbon fiber reinforcement contains 30-45 wt% carbon fiber, the carbon nanotube aerogel contains 0.5-3 wt% carbon nanotube aerogel, and the magnetically responsive particles contain 0.1-1 wt% Ni particles. Wherein: Liquid metal matrix: Liquid metal forms a three-dimensional, continuous, thermally conductive, and highly conductive network between carbon fiber reinforcements, ensuring rapid heat transfer from the heat source to the heat sink. It also reflects and absorbs electromagnetic waves. The high fluidity of the liquid metal allows it to fully fill interfacial micro-voids, significantly reducing contact thermal resistance and forming the cornerstone of the composite material's high thermal conductivity. Being liquid near room temperature, it imparts excellent deformability and interfacial bonding to the composite. During thermal cycling, the liquid state buffers stress caused by thermal expansion mismatch between the carbon fiber and the metal heat sink, preventing interfacial delamination or cracking due to rigid contact. Simultaneously, it can form metal compounds with the metal layer on the modified carbon fiber surface, achieving interfacial reactivity and gradient structure construction. Considering that the liquid metal matrix maintains the integrity of the continuous phase to perform thermal conductivity and interfacial reaction functions, while ensuring the carbon fiber reinforcement maintains a sufficient volume fraction to provide a mechanical framework and locking function, a synergistic balance between thermal conductivity, mechanical properties, and interfacial reaction is achieved. The melting point range of eutectic alloys is 5-20℃. GaInSn eutectic alloys contain 60-70% Ga, 20-25% In, and 10-15% Sn. Ga, as the base component, provides low melting point and high thermal conductivity. In, as a melting point regulating element, ensures eutectic formation and improves wettability. Sn, as a eutectic stabilizer, provides thermal stability and anti-leakage properties. The three work synergistically to form a matrix alloy system that combines low melting point, high thermal conductivity, and good chemical stability.
[0033] The liquid metal matrix may optionally contain at least one of Zn: 0.5-2wt% and Ag: 0.1-0.5wt%, wherein Zn is used to adjust the melting point and Ag is used to improve thermal conductivity.
[0034] Carbon fiber reinforcement: The carbon fiber reinforcement contains carbon fiber filaments with a diameter of 6-8 μm and a density of 1.6-1.80 g / cm³. 3 The carbon fiber surface has a Cu-Ni coating, which includes a Cu layer and a Ni layer. The Cu layer is formed on the carbon fiber surface, and the Ni layer is formed on the Cu layer surface. The thickness of the Cu layer is 0.2-0.5μm, and the thickness of the Ni layer is 0.5-2.0μm. The thickness of the Cu layer is less than the thickness of the Ni layer, thus forming a gradient coating.
[0035] The Cu layer is prepared by chemical plating or electroplating, and the Ni layer is prepared by electroplating. The surface of the Ni layer is roughened to a surface roughness Ra of 0.5-2.0 μm. The Cu layer has good adhesion to the carbon fiber surface, and the reactivity of Cu with Ga is moderate, enabling the formation of a CuGa2 intermetallic compound layer at the interface. The outer Ni layer has higher reactivity and reacts with Ga to form a NiGa3 intermetallic compound transition layer. This gradient design from the inner Cu layer to the outer Ni layer results in a gradual increase in the coefficient of thermal expansion from the carbon fiber surface outwards, forming a smooth thermal expansion gradient transition and effectively alleviating thermal stress concentration during thermal cycling. In addition, the roughening treatment of the Ni layer increases the interfacial contact area, further improving the interfacial bonding strength. The gradient Cu-Ni coating reacts in situ with the liquid metal substrate at the interface to form a gradient metallurgical bonding interface, with the CuGa2 intermetallic compound layer and the NiGa3 intermetallic compound transition layer forming sequentially from the carbon fiber surface outwards. This gradient metallurgical bonding interface achieves a smooth transition from carbon fiber to liquid metal.
[0036] Carbon nanotube aerogel: Carbon nanotube aerogels are uniformly distributed within the gaps between carbon fiber reinforcements, forming a microscopic locked network. The carbon nanotube aerogel network is prepared from multi-walled carbon nanotubes (MWCNTs) through hydrothermal self-assembly and freeze-drying processes. The MWCNTs have an outer diameter of 10-20 nm, a length of 5-20 μm, and a specific surface area of 200-400 m². 2 / g. The introduction of carbon nanotube aerogel is intended to construct a microscale liquid metal locking system: First, the large specific surface area of carbon nanotubes provides strong physical adsorption force, firmly adsorbing liquid metal molecules onto the CNT surface; second, the abundant nanoscale pores generate strong capillary forces, which can effectively bind liquid metal; third, the CNT network constructs a microscopic "liquid reservoir" system for liquid metal, so that even if the macroscopic pores expand during deformation, the liquid metal in the microscopic reservoir can still be firmly bound by capillary forces.
[0037] Ni particles: Ni particles are dispersed in a liquid metal matrix, with an average particle size of 1-10 μm, preferably 3-7 μm. During magnetic field-assisted vacuum pressure impregnation, the Ni particles act as a magnetic response medium, generating rotational motion under the action of an alternating magnetic field, thereby driving the carbon fibers to align and achieve an orderly distribution of the reinforcement. Simultaneously, the presence of Ni particles promotes uniform penetration of the liquid metal into the preform, improving impregnation efficiency. Furthermore, Ni particles can undergo interfacial reactions with Ga elements in the liquid metal matrix, further enhancing interfacial bonding.
[0038] The following details the preparation method of the carbon fiber reinforced liquid metal matrix composite material in this embodiment: S1: Gradient coating treatment on carbon fiber surface: The carbon fiber is subjected to degumming, roughening, and sensitization activation treatments in sequence. Then, a Cu layer is prepared by chemical plating, and a Ni layer is prepared by electroplating to obtain carbon fiber with a Cu-Ni coating on the surface.
[0039] S2: Preparation of carbon nanotube aerogel: Multi-walled carbon nanotubes were dispersed in deionized water, ultrasonically dispersed, and then subjected to a hydrothermal self-assembly reaction. Finally, carbon nanotube aerogels were obtained by freeze-drying.
[0040] S3: Preparation of carbon fiber preforms: The gradient-coated carbon fibers obtained in step S1 are woven into a three-dimensional braid, and the carbon nanotube aerogel obtained in step S2 is embedded in the gaps of the three-dimensional braid. A temporary adhesive is used for shaping, and after drying, a preform is obtained.
[0041] S4: Magnetic field-assisted vacuum pressure impregnation: The alternating magnetic field has a frequency of 10-100Hz and a magnetic field strength of 0.1-0.5T. The alternating magnetic field is applied in the following three stages: impregnation stage: frequency 50-100Hz, strength 0.2-0.5T; reaction stage: frequency 10-50Hz, strength 0.1-0.3T; curing stage: frequency 10-30Hz, strength 0.1-0.2T. The preheating temperature of the preform is 100-150°C, the preheating temperature of the liquid metal is 50-80°C higher than the alloy melting point, the vacuum degree is <10Pa, the vacuum holding time is 10-15min, the impregnation pressure is 1-5MPa, the holding time is 10-30min, and the cooling rate is 5-10°C / min.
[0042] The preform obtained in step S3 is placed in a mold. Under the action of an alternating magnetic field, liquid metal containing Ni microparticles is vacuum pressure impregnated into the preform. Under the combined action of the magnetic field and pressure, it is cooled and solidified to obtain a carbon fiber reinforced liquid metal matrix composite material.
[0043] S5: Post-processing: The composite material obtained in step S4 is subjected to surface treatment to obtain the final composite material.
[0044] Examples and comparative examples: Liquid metal A1: GaInSn eutectic alloy Ga 67 In 22 Sn 11 Prepared from A2, A3, and A4; A2: Gallium (Ga), produced by Zhuzhou Keneng New Materials Co., Ltd. (Ga-5N). A3: Indium (In), produced by Liuzhou Zhongyin Technology Co., Ltd. (In-5N). A4: Metallic tin (Sn), produced by Yunnan Tin Industry Co., Ltd. (Sn-4N).
[0045] Melting point modifier B1: Metallic zinc, Zn-4N produced by Zhuzhou Smelter Group. B2: Metallic silver Ag, Ag-4N produced by China Silver Group.
[0046] Carbon fiber C1: Carbon fiber, Toray Industries, Japan, T700S-12K-50C carbon fiber, with a single filament diameter of 7μm and a density of 1.81g / cm³. 3 Tensile strength 4900MPa C2: Carbon fiber, T800HB carbon fiber produced by Toray Industries, Japan, with a single filament diameter of 5μm and a density of 1.78g / cm³. 3 Tensile strength 5490MPa;
Carbon fiber tubing aerogel
[0047]
Magnetic Response Particles
[0048] Table 1: Example 1: Prepared according to the formulation shown in Table 1, following the steps below. S1: Take raw material C1 (T700S carbon fiber), and sequentially perform degumming and roughening (60℃ concentrated nitric acid for 2 hours), followed by electroless copper plating (CuSO4 15g / L, formaldehyde 15mL / L, EDTA 30g / L, pH 12.5, 60℃, deposition 0.35µm), and electroplating with nickel (NiSO4 250g / L, NiCl2 45g / L, H3BO3 35g / L, pH 4.5, 55℃, 2A / dm). 2 Ra1.25µm was obtained by deposition of 1.25µm and micro-blasting (Al2O3 2µm, 0.2MPa, 30s).
[0049] S2: Take raw material D (MWCNT), disperse 1 mg / mL in deionized water, sonicate at 500 W for 2 h, self-assemble in a hydrothermal reactor at 150 °C for 12 h, and freeze-dry at -50 °C / <10 Pa for 48 h to obtain an aerogel (density approximately 15 mg / cm³). 3 (Porosity > 99%).
[0050] S3: Gradient coated carbon fiber three-dimensional five-directional weaving (weaving angle 22°, fiber volume fraction 42%), embedded with S2 aerogel, 5% PVA for shaping, dried at 80℃ for 4h.
[0051] S4: Preheat the preform at 120℃ for 2 hours. Weigh A2 / A3 / A4 according to Ga 67% / In 22% / Sn 11%, melt them under Ar atmosphere to obtain A1, superheat to 70℃, ultrasonically disperse raw material E (0.55wt%) for 30 minutes, vacuum the mold <10Pa for 12 minutes, apply 3MPa for impregnation, and use an alternating magnetic field in three stages: impregnation stage 80Hz / 0.35T / 15min → reaction stage 30Hz / 0.2T / 20min → curing stage 20Hz / 0.15T / 15min, with a cooling rate of 7℃ / min.
[0052] S5: Remove excess liquid metal, clean with ethanol, trim edges, and apply a silicone protective layer (0.1mm).
[0053] Example 2: Compared with Example 1, the changes are as follows: the content of raw material A1 is reduced from 58.5 wt% to 50.0 wt%, the content of raw material C1 is increased to 47.0 wt%, and the rest remain unchanged.
[0054] Preparation differences: The liquid metal content is low, the vacuum holding time is extended to 15 min; the impregnation pressure is increased to 4 MPa; the magnetic field strength during the curing stage is reduced to 0.1 T to avoid uneven distribution of liquid metal.
[0055] Example 3: Compared with Example 1, the changes are: the content of raw material A1 is increased to 68.0 wt%, and the content of raw material C1 is reduced to 29.0 wt%.
[0056] Preparation differences: Vacuum holding time was shortened to 8 min; impregnation pressure was reduced to 2 MPa; impregnation stage frequency was increased to 90 Hz to promote fiber orientation.
[0057] Example 4: Compared with Example 1, the changes are: the content of raw material C1 is reduced to 30.0 wt%, and the content of raw material A1 is increased to 67.7 wt%.
[0058] Preparation differences: lower carbon fiber content, higher porosity, and shorter impregnation time; pressure holding time extended to 25 min to ensure stability of liquid metal.
[0059] Example 5: Compared with Example 1, the changes are as follows: the content of raw material C1 is adjusted to 35.0 wt% (the median value of the claim), and the content of raw material A1 is reduced to 62.7 wt%.
[0060] Preparation differences: The carbon fiber content is at an intermediate level, the skeleton density is moderate, the impregnation pressure is maintained at 3MPa, and the holding time is extended to 22min to ensure that the liquid metal is fully filled.
[0061] Example 6: Compared with Example 1, the changes are: the content of raw material C1 is increased to 45.0 wt%, and the content of raw material A1 is reduced to 52.7 wt%.
[0062] Preparation differences: Low porosity and long and narrow pores, impregnation pressure increased to 5 MPa (upper limit), and holding time extended to 30 min.
[0063] Example 7: Compared to Example 1, the changes are: Ga 60%, In 25%, Sn 10% in A1. B1 and B2 are not added.
[0064] Preparation differences: The alloy has a melting point of approximately 8°C and better fluidity. Increasing the preheating temperature of the preform to 130°C reduces the effective viscosity. The low Sn content results in a slightly wider solidification range, and the cooling rate is controlled at 5°C / min to ensure sufficient interfacial reaction.
[0065] Example 8: Compared to Example 1, the changes were as follows: Ga 70%, In 20%, Sn 15% in A1; 1.0 wt% B1 (Zn) and 0.3 wt% B2 (Ag) were added. The A1 content was adjusted accordingly to 58.4 wt%.
[0066] Preparation differences: Five elements are melted simultaneously and magnetically stirred for 2 hours to ensure uniformity. The alloy melting point is about 15℃, and the superheat is adjusted to 65℃ during impregnation.
[0067] Example 9: Compared with Example 1, the changes are: the content of raw material D is reduced to 0.5 wt% (lower limit), and the content of raw material A1 is increased to 59.15 wt%.
[0068] Preparation differences: less aerogel is used, requiring more precise cutting and placement during embedding, and the cooling rate during the curing stage is reduced to 5℃ / min to compensate for insufficient microscopic locking.
[0069] Example 10: Compared with Example 1, the changes are: the content of raw material D is increased to 3.0 wt%, and the content of raw material A1 is reduced to 57.0 wt%.
[0070] Preparation differences: Higher CNT content, increased impregnation pressure to 5MPa, extended holding time to 30min, and extended hydrothermal reaction time to 18h.
[0071] Example 11: Compared with Example 1, the changes are: the content of raw material E is reduced to 0.1 wt%, and the content of raw material A1 is increased to 59.35 wt%.
[0072] Preparation differences: The Ni particle content is extremely low, the magnetic response is weak, and the magnetic field during the impregnation stage is increased to 100Hz / 0.5T compensation.
[0073] Example 12: Compared with Example 1, the changes are: the content of raw material E is increased to 1.0 wt%, and the content of raw material A1 is reduced to 58.2 wt%.
[0074] Preparation differences: Higher Ni particle content results in stronger magnetic response; the magnetic field during impregnation is reduced to 60Hz / 0.3T to avoid excessive stirring. The Ni particle dispersion time is extended to 45min.
[0075] Example 13: Compared with Example 1, the changes are: Cu layer 0.2µm, Ni layer 0.5µm, Ra 0.5µm.
[0076] Preparation differences: chemical copper plating for 20 min, electroplating nickel for 20 min, micro-blasting for 15 s, and the magnetic field was reduced to 20 Hz during the reaction stage to avoid damaging the thin plating layer.
[0077] Example 14: Compared with Example 1, the changes are: Cu layer 0.5µm, Ni layer 2.0µm, Ra 2.0µm.
[0078] Preparation differences: electroless copper plating for 50 min, electroplating nickel for 80 min, micro-blasting for 60 s (5µm Al2O3), and the reaction stage was extended to 30 min.
[0079] Example 15: Compared with Example 1, the changes were: 0.5 wt% B1 (Zn) was added, and the amount of raw material A1 was reduced to 58.0 wt%.
[0080] Preparation differences: During the preparation of S4 alloy, B1 and A2 / A3 / A4 are melted simultaneously, and the alloy melting point is about 12.5℃ (slightly higher than Example 1).
[0081] Example 16: Compared with Example 1, the change was: 0.5 wt% B2 (Ag) was added, and the amount of raw material A1 was reduced to 58.2 wt%.
[0082] Preparation differences: The Ag content is higher, and the magnetic stirring time is extended to 3 hours to ensure complete dissolution.
[0083] Example 17: Compared with Example 1, the changes are as follows: the raw material D parameter is set to the lower limit, with an outer diameter of 10 nm, a length of 5 µm, and a specific surface area of 200 m². 2 / g.
[0084] Preparation differences: Ultrasonic power was reduced to 400W, hydrothermal temperature was 120℃, and time was 8h.
[0085] Example 18: Compared with Example 1, the changes are: outer diameter of raw material D is 20 nm, length is 20 µm, and specific surface area is 400 m². 2 / g.
[0086] Preparation differences: Ultrasonic time was extended to 3 h, hydrothermal treatment at 180℃ for 16 h was performed, and the outer diameter and specific surface area of MWCNT were changed.
[0087] Example 19: Compared with Example 1, the change is that the average particle size of raw material E is increased from 5µm to 10µm.
[0088] Preparation differences: Larger particles settle faster, dispersion time is shortened to 20 min, average particle size (E) is changed, and impregnation is performed immediately after dispersion. The magnetic field during impregnation is increased to 90 Hz.
[0089] Example 20: The formulation is exactly the same as in Example 1. This example focuses on verifying C1 (T700S, density 1.81 g / cm³). 3 Applicability of ).
[0090] Preparation differences: Same as in Example 1.
[0091] Example 21: Compared with Example 1, the change is: the raw material is changed from C1 (T700S, Φ7µm, 1.81g / cm). 3 Replace with C2 (T800HB, Φ5µm, 1.78g / cm). 3 The rest of the recipe remains unchanged.
[0092] Preparation differences: C2 has a smaller diameter (5µm), and the weaving tension is appropriately reduced. The sensitization and activation time of S1 is extended to 1.5h.
[0093] Comparative Examples 1-8 Comparative Example 1: Compared with Example 1, only the A1 content was reduced from 58.5% to 40.0%, while the C1 content was increased to 57.0%.
[0094] Preparation differences: The impregnation pressure was increased to 5 MPa and the pressure was maintained for 30 min.
[0095] Comparative Example 2: Compared to Example 1, only the A1 content was increased to 75.0%, while the C1 content was decreased to 22.0%.
[0096] Comparative Example 3: Compared to Example 1, only the C1 content was reduced to 25.0%, while the A1 content was increased to 72.0%.
[0097] Comparative Example 4: Compared to Example 1, only the C1 content was increased to 50.0%, while the A1 content was decreased to 46.5%.
[0098] Preparation differences: Impregnation pressure of 5MPa and holding pressure for 30min was still not complete.
[0099] Comparative Example 5: Compared to Example 1, without the addition of ingredient D (CNT=0), A1 increased to 60.25%.
[0100] Comparative Example 6: Compared to Example 1, without the addition of raw material E (Ni=0), Al increased to 59.05%. No magnetic field was applied in step S4.
[0101] Comparative Example 7: The formulation is the same as in Example 1, but S1 only prepares a Cu layer (0.35µm) and does not prepare a Ni layer.
[0102] Comparative Example 8: Compared to Example 1, the Ga content in A1 decreased from 67% to 55% (below the lower limit of 60%), while the remaining components remained unchanged.
[0103] Preparation differences: The alloy has a melting point of about 28°C, and it is still difficult to increase the impregnation temperature to 160°C.
[0104] The following tests were performed on the composite material. Unless otherwise specified, all tests were conducted at 25°C. The main indicators are as follows: 1. Thermal conductivity (W / (m•K)): Tested using the laser scintillation method according to ASTM E1461-13, with a sample size of 10mm × 2mm; 2. Bending strength (MPa): Tested according to GB / T1447-2005, with a sample span-to-thickness ratio of 16:1, a loading rate of 2 mm / min, and a sample size of 80 mm × 10 mm × 2 mm. 3. Electromagnetic shielding effectiveness (dB): Tested according to ASTM D4935-10. The sample is annular: outer diameter 133mm, inner diameter 6.35mm, test band range 8.2-18GHz, frequency 30MHz-6GHz. 4. Thermal retention rate after 1000 cycles (%): Tested according to ASTM E1461-13 (laser flash method), thermal conductivity decay rate = [(λ0-λ n ) / λ0]×100%.
[0105] 5. Liquid metal retention rate (%): Tested according to ASTM D1653-13, held for 15 min at -40℃ to 150℃, with a temperature rise / fall rate of 10℃ / min. Liquid metal retention rate = (sample mass after cycle / sample mass before cycle) × 100%.
[0106] Table 2: Within the range of the formulation, the dual-scale liquid metal locking system in this embodiment fully plays its role: macroscopically, the three-dimensional woven carbon fiber skeleton forms a stable mechanical interlocking structure with the liquid metal, and microscopically, the CNT aerogel achieves microscopic locking through capillary adsorption and the liquid reservoir effect; at the same time, the gradient interface reaction layer (CuGa2+NiGa3) effectively mitigates the CTE mismatch between the carbon fiber and the liquid metal. Therefore, the material in this embodiment exhibits excellent comprehensive performance: thermal conductivity 55~95W / (m•K), flexural strength 168~312MPa, electromagnetic shielding effectiveness 55~75dB, and after 1000 thermal cycles of -40℃~150℃, the retention rate is ≥99.4% and the thermal conductivity decay is ≤3.2%, demonstrating excellent long-term reliability.
[0107] In the comparative examples, when the Al content was below 50 wt% (Comparative Example 1), the liquid metal was insufficient to fully impregnate the carbon fiber skeleton, resulting in a thermal conductivity of only 18 W / (m•K); when the Al content was above 68 wt% (Comparative Example 2), the excessive matrix caused the bending strength to drop sharply to 85 MPa; when the carbon fiber content was below 30 wt% (Comparative Example 3), the sparse skeleton resulted in a shielding effectiveness of only 42 dB and severe liquid metal loss (retention rate of 93.5%); when the carbon fiber content was above 45 wt% (Comparative Example 4), the excessive filling of pores resulted in a thermal conductivity of only 35 W / (m•K); in addition, without CNT aerogel (Comparative Example 5), micro-locking failure occurred, and the retention rate after 1000 cycles was only 95.8%; without Ni particles (Comparative Example 6), the gradient interface could not be formed, and the thermal conductivity decreased by as much as 4.5%; the absence of Ni coating (Comparative Example 7) and the excessively low Ga content (Comparative Example 8) also led to poor interfacial bonding and abnormal alloy melting point, respectively.
[0108] The above embodiments are only for illustrating the technical concept and features of the present invention, and are intended to enable those skilled in the art to understand the content of the present invention and implement it accordingly. They should not be construed as limiting the scope of protection of the present invention. All equivalent changes or modifications made in accordance with the spirit and essence of the present invention should be covered within the scope of protection of the present invention.
Claims
1. A carbon fiber reinforced liquid metal matrix composite material, characterized in that: include: Liquid metal matrix: Contains 50-68 wt% GaInSn eutectic alloy; Carbon fiber reinforcement: containing 30-45 wt% carbon fiber, wherein the surface of the carbon fiber has a Cu-Ni coating, the Cu-Ni coating comprising a Cu layer and a Ni layer, wherein the Cu layer is formed on the surface of the carbon fiber, the Ni layer is formed on the surface of the Cu layer, and the thickness of the Cu layer is less than the thickness of the Ni layer; Carbon nanotube aerogel: comprising 0.5-3 wt% carbon nanotube aerogel, wherein the carbon nanotube aerogel is used to distribute in the gaps of the carbon fiber reinforcement; Magnetic responsive particles: comprising 0.1-1 wt% Ni particles, wherein the Ni particles are dispersed in the liquid metal matrix.
2. The carbon fiber reinforced liquid metal matrix composite material according to claim 1, characterized in that: The GaInSn eutectic alloy comprises Ga: 60-70%, In: 20-25%, and Sn: 10-15%.
3. The carbon fiber reinforced liquid metal matrix composite material according to claim 1 or 2, characterized in that: The liquid metal matrix further comprises at least one of Zn: 0.5-2wt% and Ag: 0.1-0.5wt%.
4. The carbon fiber reinforced liquid metal matrix composite material according to claim 1, characterized in that: The carbon fiber reinforcement has a single carbon fiber filament diameter of 6-8 μm and a density of 1.6-1.80 g / cm³. 3 ; The thickness of the Cu layer is 0.2-0.5 μm; The Ni layer has a thickness of 0.5-2.0 μm and a surface roughness Ra of 0.5-2.0 μm.
5. The carbon fiber reinforced liquid metal matrix composite material according to claim 1, characterized in that: The carbon nanotube aerogel comprises multi-walled carbon nanotubes with an outer diameter of 10-20 nm, a length of 5-20 μm, and a specific surface area of 200-400 m². 2 / g.
6. The carbon fiber reinforced liquid metal matrix composite material according to claim 1, characterized in that: The average particle size of the Ni particles is 1-10 μm.
7. A method for preparing the carbon fiber reinforced liquid metal matrix composite material according to any one of claims 1 to 6, characterized in that: include: Carbon fiber reinforcements are woven into a three-dimensional braid, and carbon nanotube aerogels are embedded in the gaps between the three-dimensional braids. After shaping and drying, a preform is obtained. Under the action of an alternating magnetic field, liquid metal containing Ni particles is vacuum pressure impregnated into a preform. The Cu-Ni coating on the carbon fiber surface reacts in situ with the liquid metal matrix at the interface to form a metallurgical bonding interface. The metallurgical bonding interface consists of CuGa2 layer and NiGa3 layer from the carbon fiber surface outward. Under the synergistic effect of magnetic field and pressure, the mixture is cooled and solidified to obtain a carbon fiber reinforced liquid metal matrix composite material.
8. The preparation method according to claim 7, characterized in that: The preparation method further includes sequentially performing degumming, roughening, and sensitization activation treatments on the carbon fiber, preparing a Cu layer by chemical plating, and preparing a Ni layer by electroplating to obtain carbon fiber with a Cu-Ni coating on the surface.
9. The preparation method according to claim 7, characterized in that: The preparation method further includes dispersing multi-walled carbon nanotubes in deionized water, performing hydrothermal self-assembly reaction after ultrasonic dispersion, and then freeze-drying to obtain carbon nanotube aerogel.
10. The preparation method according to claim 7, characterized in that: The alternating magnetic field has a frequency of 10-100Hz and a magnetic field strength of 0.1-0.5T. The alternating magnetic field is applied in the following three stages: (a) Impregnation stage: frequency 50-100Hz, intensity 0.2-0.5T; (b) Reaction stage: frequency 10-50Hz, intensity 0.1-0.3T; (c) Curing stage: frequency 10-30Hz, strength 0.1-0.2T.
11. The preparation method according to claim 7, characterized in that: The specific parameters for vacuum pressure impregnation are as follows: preheating temperature of the preform is 100-150℃; the melting point range of the liquid metal is 5-20℃, and its preheating temperature is 50-80℃ higher than the melting point; vacuum degree is <10Pa, vacuum holding time is 10-15min; impregnation pressure is 1-5MPa, holding time is 10-30min, and cooling rate is 5-10℃ / min.
12. The preparation method according to claim 7, characterized in that: The preparation method further includes a step of surface treatment of the carbon fiber reinforced liquid metal matrix composite material.
13. The application of the carbon fiber reinforced liquid metal matrix composite material according to any one of claims 1-6 in thermal interface materials or electromagnetic shielding materials.
Citation Information
Patent Citations
Liquid metal / carbon fiber composite material and preparation method and application thereof
CN108457079A
Preparation method of carbon fiber reinforced high-strength and high-thermal-conductivity composite film
CN113402288A
Liquid metal thermal interface material and preparation method thereof
CN116554842A